Impact of bariatric surgery on cytochrome P 450 enzyme activity - Pham, Anna; Chan, Patrick; Mercado, Angela; Wang, Jeffrey; Wang, Zhijun; Ibrahim, Hajer; Gogineni, Hyma; Huang, Ying (Frontiers in Pharmacology, 2024)
Bariatric surgeries are becoming more prevalent as obesity rates continue to rise. Being that it is an effective weight-loss procedure, it can induce significant anatomical, physiological, and metabolic alterations, which affect the pharmacokinetics of various medications. Cytochrome (CYP) P450 is a group of enzymes that are primarily responsible for metabolizing most medications. Bariatric surgery may affect CYP activity and consequently alter metabolism of various medications, and the resulting weight loss may influence the metabolism of various drugs. This study investigates the impact of bariatric surgery on which CYP enzymes are affected and their effects medications. Authors of this study did an extensive literature review and research in databases including PubMed and EMBASE. The evidence was gathered for medication efficacy influenced by enzyme fluctuations to advocate for further studies for patients that undergo bariatric surgery. The search was limited to English-language results and is deemed up to date as of September 2023. There are numerous studies that indicated alterations of the CYP enzyme activity, which affects the pharmacokinetics of medications used to treat acute and chronic conditions after bariatric surgery. There are various mechanisms involved in CYP enzyme activity leading to fluctuations and the clearance of medications and subsequently compromising the efficacy and safety of these agents. It is imperative to conduct more prospective randomized control studies with longer duration to guide clinicians on how to manage medications with various CYP activity for patients' post-bariatric surgery.